The Photomodulation Activity of Metformin Against Oral Microbiome - Afrasiabi, Shima; Pourhajibagher, Maryam; Bahador, Abbas (Journal of Lasers in Medical Sciences, 2019)
Periodontitis is one of the most common inflammatory diseases of the periodontium, which results in the inflammatory destruction of supporting structures around teeth and is closely associated with the development of systemic disease. Due to a wide variety of antibiotic resistance periodontopathic bacteria, photodynamic therapy (PDT) is a non-invasive adjunctive therapeutic modality that is capable of destroying the whole range of microbes. Metformin (Metf) is an antidiabetic drug, and recent studies suggest that cancer patients who receive Metf and are exposed to radiotherapy and chemotherapy show better outcomes. Our surveys in this review introduce Metf as a potent stimulus in increasing the efficacy of PDT in the induction of destruction in microbial cells.